1,25-D3 attenuates cerebral ischemia injury by regulating mitochondrial metabolism via the AMPK/AKT/GSK3β pathway - Li, Yutian; Li, Xiangling; Xu, Shuangli; Zhao, Yingzhe; Pang, Meng; Zhang, Xiaojun; Wang, Xuejian; Wang, Yanqiang (Frontiers in Aging Neuroscience, 2022)
The brain injury caused by cerebral ischemia-reperfusion (IR) is related to mitochondrial damage. Maintaining the normal function of mitochondria, promoting angiogenesis, protecting neuronal cells and resisting oxidative stress are the hinge to functional recovery after acute ischemic stroke. Investigating the role of 1α, 25-dihydroxyvitamin D3 (VitD or 1,25-D3) on mitochondrial function in rats with cerebral ischemia-reperfusion injury through AMPK/Akt/GSK-3β signaling pathway using middle cerebral artery occlusion (MCAO) model. Test the neurologic function and determine infarct size, respectively. HE, NeuN and Nissl stainings were conducted to observe the morphology and number of the cerebral cortical neurons. Then p-AMPK, vitamin D receptor (VDR), p-GSK-3β, p-Akt, P53, Caspase-3, cytochrome C (CytC), TGF-β and VEGF in mitochondria were analyzed by Western blotting. Succinate dehydrogenase (SDH), ATPase, reactive oxygen species (ROS), malondialdehyde (MDA) were detected by kits. RT-qPCR was used to analyze TGF-β, VEGF, P53 and CytCmRNA. The results demonstated that the cerebral infarct volume, neurological function score, apoptotic proteins P53, CytC, caspase-3 were significantly increased in MCAO. 1,25-D3 reduced the infarct size, neurological function score, up-regulated the TGF-β, p-AMPK, p-Akt, p-GSK-3β, VDR and VEGF, down-regulated P53, CytC and Caspase-3. Pyridoxal-5-phosphate (P5P), as an antagonist of VDR, could partially block the neuroprotective effect of 1, 25-D3. In conclusion, 1,25-D3 activated AMPK/Akt/GSK-3β signaling, VDR, inhibited P53, CytC, and Caspase-3, increased TGF-β and VEGF, regulated mitochondrial metabolism, reduced neuronal apoptosis, promoted vascular growth, exerted neuroprotective effects on stroke. These findings suggested that this signaling pathway may be an effective target for the treatment of ischemic stroke.